Going Clubbing in the Eighties: Convergence in Manufacturing Sectors at a Glance - Silvia Dal Bianco (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2010)
I adopt the distribution dynamics framework to study labor productivity convergence, in the period 1980-1995, among 28 developed and developing countries, in different manufacturing sub-sectors, identified, as according their technological content into Resource Based, Low Technology, Medium Technology and High Technology. I find that, exception made for High Technology and Manufacturing as a whole, all subcompartments are predicted to converge within small groups, validating the so-called club-convergence hypothesis. Thus, as high tech sectors are the ones opening the best growth-equity prospects, developing countries should target these kind of productions.
Keywords: C14; O33; O47; 330; Italian Regions; Neoclassical and Technological Convergence; Distribution Dynamics